Dual-site cooperation for synergistic optimization of the band structure and spin state to facilitate C–N coupling reaction - Qizhu Qian; Qilong Liu; Mengxiang Wang; Jingjing Yang; Huiyi Li; Wei Bai; Wentao Wang; Changzheng Wu; Chong Xiao; Yi Xie (Proceedings of the National Academy of Sciences, 2025)
The emerging electrocatalytic C–N coupling reaction provides an attractive route toward green urea synthesis, but a lack of in-depth insight into the catalytic mechanism and the geometric/electronic configurations that determine the key C- and N-coupling intermediates formation hampers the exploration of efficient catalysts. Herein, we design a bimetallic oxide (Fe-Mo-O) with dual active sites of Fe and Mo for the adsorption and activation of NO 2 − and CO 2 , respectively. Constructing dual-metal catalyst leads to an upshift of the d-band center and the generation of an intermediate-spin Fe center, which not only favors the selective conversion of *CO 2 into the key intermediate *CO on Mo sites, but also facilitates the adsorption and reduction of NO 2 − on Fe sites. Operando characterizations and theoretical calculations together elucidate that urea generation is associated with the formation of *CONH 2 intermediate by coupling *CO and *NH 2 on the alternating Mo and intermediate-spin Fe active sites, ultimately synergistically lowering the C–N coupling energy barrier. Specifically, the Fe-Mo-O catalyst delivers a high urea yield rate of 681.8 μg h −1 mg −1 cat. and an excellent Faradaic efficiency of 60% at −0.5 V (vs. RHE). Furthermore, a C–N coupling paired with a glycerol oxidation system allows for energy-saving electrochemical coproduction of urea and formic acid. Our findings offer a feasible strategy to develop cutting-edge electrocatalysts for urea synthesis by active site design and electronic structure regulation.